IPTEKS BERBASIS INKUBASI INOVASI DAN DUNIA USAHA: MARKET RESEARCH PRODUK-PRODUK INOVASI UNIVERSITAS ANDALAS - Berri Brilliant Albar; Indah Maya Sari; Mayang Larasati; Sapta Eka Putra (LPPM Universitas Andalas, 2020)
Universitas Andalas innovative products enter the next stage in the series of product development processes leading to commercialization. As a product in the period of development, market research needs to be done to determine consumer preferences and perceptions, to be the basis of business analysis and improvement. For this reason, community service activities are needed to help inventors, developers and partners in researching the market and knowing the preferences of prospective customers as one of the Innovation and Business-based Science and Technology (IbIIDU) incubation programs. This activity is carried out through deep interviews with inventors, product / sample tests and simulations, surveys and observations on the market and its segmentation. Market research techniques are used by searching, gathering, and analysing information about consumers or markets that are appropriate for the business they run. In addition to product quality through understanding the needs and tastes of consumers, another thing that also builds consumer ratings of products is perception. Positioning is the initial analysis to build perception in the minds of consumers. This activity aims to obtain market research documents to determine consumer perceptions about innovation products after consuming the product so that it can be used as a reference for product improvement before commercialization. This activity also aims to help to analyse positioning and design marketing strategies for the next stage. Understanding consumer needs and creating products that are able to meet the needs and solve consumer problems are the keys to successful product commercialization. This activity carried out market research on 7 Andalas University innovation products on food and beverage category with 100 respondents for each of their products spread across the West Sumatra region. This activity produces product market research documents that can be used by each inventor and developer of each product to develop and commercialize their products.